2018
DOI: 10.1097/sla.0000000000002181
|View full text |Cite
|
Sign up to set email alerts
|

Decellularization of the Porcine Ear Generates a Biocompatible, Nonimmunogenic Extracellular Matrix Platform for Face Subunit Bioengineering

Abstract: Acellular scaffolds were produced from the porcine ear, and may be a valuable platform to treat facial deformities using regenerative medicine approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 36 publications
4
45
0
Order By: Relevance
“…Despite robust initial recellularization, subsequent growth, and proliferation observed in all cell types with no obvious differences between cells seeded onto wild‐type versus α‐Gal KO lungs, these findings certainly raise concerns for clinical translation. A recent study on face subunit bioengineering, however, showed that ECM scaffolds obtained from the porcine ear may be nonimmunogenic . In fact, when implanted in discordant pigs, such scaffolds did not trigger any specific anti‐swine leukocyte antigen (SLA) humoral response, as demonstrated by a lack of donor‐specific antibodies.…”
Section: Scaffolds From Xenogenic and Allogeneic Organsmentioning
confidence: 99%
“…Despite robust initial recellularization, subsequent growth, and proliferation observed in all cell types with no obvious differences between cells seeded onto wild‐type versus α‐Gal KO lungs, these findings certainly raise concerns for clinical translation. A recent study on face subunit bioengineering, however, showed that ECM scaffolds obtained from the porcine ear may be nonimmunogenic . In fact, when implanted in discordant pigs, such scaffolds did not trigger any specific anti‐swine leukocyte antigen (SLA) humoral response, as demonstrated by a lack of donor‐specific antibodies.…”
Section: Scaffolds From Xenogenic and Allogeneic Organsmentioning
confidence: 99%
“…10,11 Decellularized ECM therapies continue to be investigated through clinical trials, addressing a multitude of application anatomic sites, including the trachea, heart valves, eye, and bladder among many others. 12 Furthermore, complex structural ECM scaffolds generated from perfusion decellularization, such as heart, 13,14 lung, 15 kidney, 16 or face, 17 are within the foreseeable pipeline for future clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that well-decellularized scaffolds are poorly, if not at all, immunogenic and possibly tolerogenic, while non-well-decellularized tissues are prone to inflammatory response and degradation or encapsulation [24-27]. …”
Section: Discussionmentioning
confidence: 99%